Does Continuous Hospice Care Help Patients Remain at Home? - Casarett, David; Harrold, Joan; Harris, Pamela S.; Bender, Laura; Farrington, Sue; Smither, Eugenia; Ache, Kevin; Teno, Joan (Journal of pain and symptom management, 2015)
In the U. S., hospices sometimes provide high-intensity “continuous care” in patients' homes. However, little is known about the way that continuous care is used or what impact continuous care has on patient outcomes. To describe patients who receive continuous care and determine whether continuous care reduces the likelihood that patients will die in an inpatient unit or hospital. Data from 147,137 patients admitted to 11 U.S. hospices between 2008 and 2012 were extracted from the electronic medical records. The hospices are part of a research-focused collaboration. The study used a propensity score-matched cohort design. A total of 99,687 (67.8%) patients were in a private home or nursing home on the day before death, and of these, 10,140 (10.2%) received continuous care on the day before death. A propensity score-matched sample (n = 24,658) included 8524 patients who received continuous care and 16,134 patients who received routine care on the day before death. Using the two matched groups, patients who received continuous care on the day before death were significantly less likely to die in an inpatient hospice setting (350/8524 vs. 2030/16,134; 4.1% vs. 12.6%) (odds ratio [OR] 0.29; 95% CI 0.27–0.34; P < 0.001). When patients were cared for by a spouse, the use of continuous care was associated with a larger decrease in inpatient deaths (OR 0.12; 95% CI 0.09–0.16; P < 0.001) compared with those patients cared for by other family members (OR 0.37; 95% CI 0.32–0.42; P < 0.001). It is possible that unmeasured covariates were not included in the propensity score match. Use of continuous care on the day before death is associated with a significant reduction in the use of inpatient care on the last day of life, particularly when patients are cared for by a spouse.